Femoral venoarterial extracorporeal membrane oxygenation using a novel biatrial cannula for venous drainage and left ventricular venting. Issue 12 (1st October 2020) - Orozco‐Hernandez, Erik J.; Ahmed, Mustafa I.; Von Meering, Greg; Mcelwee, Samuel K.; Prejean, Shane P.; Gongora, Enrique; Hoopes, Charles W.
Abstract: Extracorporeal life support (ECLS) is an expanding technology for patients in cardiogenic shock. The majority of patients requiring ECLS can be managed with percutaneous venoarterial (VA) femoral cannulation. Despite sufficient extracorporeal circulatory support, a unclear number of patients develop left ventricular distension which can result in increased wall tension and stress as well as worsening pulmonary edema. Indications to vent the left ventricle can be controversial. When venting is indicated, a number of additional procedures may be considered including inotropic support, intra‐aortic balloon pump, impella, balloon atrial septostomy, or placement of a transseptal cannula. We present a unique case of a femoral VA extracorporeal membrane oxygenation as a bridge to transplant with left‐sided venting using a Bio‐Medicus NextGen cannula (Medtronic) with a transseptal approach.